Marriage and LLF. Issue 1 (1st January 2023) - Starr, Rachel
Abstract : This article considers how recent texts on marriage and relationships from the Methodist Church in Britain ( God in Love Unites Us ) and Church of England ( Living in Love and Faith ) engage with Christian traditions of marriage and asks how such traditions might be reimagined so that they help rather than hinder women in resisting domestic violence.